(untitled) (Research, Society and Development, 2021)
The article aims to analyze congenital anomalies caused by viruses, with a specific focus on Zika viruses (Zikavirus), rubella virus (Rubivirus), HIV (Human Immunodeficiency Virus) and cytomegalovirus. The method used was a qualitative review of scientific articles, performed by means of an electronic search in the database of published articles and scielo for: index, title, using the keywords in English: malformations, viruses, congenital malformation, prevalence and incidence, zika virus, cytomegalovirus. The results demonstrate the prevalence of four infectious agents in the genesis of the main congenital malformations today. Therefore, we conclude the need to know these diseases and their manifestations in depth in order to, based on such knowledge, implement them as correct medical procedures.